(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to problems in the direction of improving the system of formation and development of the creative activities of future educators through personality-oriented education, aimed at realizing the need to create the necessary conditions for the content and essence of this activity and the manifestation of the creative, mental and intellectual potential of the subjects of pedagogical processes in order to achieve.